FEATURES OF MODERN UKRAINIAN RULING POLITICAL ELITE FORMING - Кашаба, О.Ю. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The current status of the ruling political elite is analized, the features of its formation are outlined, the major route of transformation is emphasized. It is noted that the true elite in Ukraine is only being formed . The administrative elite if it wants to play the role of the political class has to posses a political culture that is to know professionally the laws of social and political state system, be able to apply professionally this knowledge in its own field and establish professionally the relationships with its colleagues.